Problems of theoretical physics. Scientific works. Issue 5 - Zagorodny, Anatoly Hlibovych; Averkov, Yurij Olegovich; Buts, Vyacheslav Aleksandrovich; Fesenko, Vollodymyr Ivanovitch; Girka, Igor Oleksandrovych; Kuklin, Volodymyr Michailovich; Prymak, Aleksey Victorovich; Slyusarenko, Yurii Viktorovych; Vavriv, Dmytro Mikhailovich; Yakovenko, Volodymyr Mefodievich; Yanovsky, Volodymytr Volodymyrovich; Загородній, Анатолій Глібович; et al. (Харків : Харківський національний університет імені В.Н. Каразіна, 2023)
The elementary and collective processes of interaction of charged particles in strong fields are discussed, in particular resonances, their regular and chaotic dynamics in regular and random fields. The mechanisms of excitation of electromagnetic oscillations by flows of nonrelativistic charged particles moving along dielectric and plasma-like media are discussed. Using the method of the so-called reduced description of nonequilibrium processes in nonlinear open systems of identical particles, in particular, at the kinetic stage of their evolution, a procedure for deriving kinetic equations for the cases of weak interaction between particles and a low intensity of the external field is described. Various scenarios are presented for the evolution of populations of strategies with memory interacting with each other within the framework of an iterated dilemma of prisoners in open and closed systems. The main attention is paid to collective characteristics such as memory, level of aggressiveness and complexity. The fine structure of the resonant regions for Alfvén and fast magnetosonic waves, which are used for RF heating in CTS in fusion devices, is discussed. The modification of the electrodynamic properties of media, which became possible after the advent of technologies that made it possible to create various inclusions in such media, is discussed. Metamaterials are studied, in particular, layered structures of ferrite semiconductors or thin wires embedded in a matrix. For scientists in the field of natural sciences, teachers, graduate students and senior students of physical faculties.

Обговорюються елементарні та колективні процеси взаємодії заряджених частинок у сильних полях, зокрема резонанси, їх регулярна та хаотична динаміка у регулярних та випадкових полях. Обговорюються механізми збудження електромагнітних коливань потоками нерелятивістських заряджених частинок, що рухаються вздовж діелектричних та плазмоподібних середовищ. Методом так званого скороченого опису нерівноважних процесів у нелінійних відкритих системах тотожних частинок, зокрема на кінетичному етапі їх еволюції, описано процедуру виведення кінетичних рівнянь для випадків слабкої взаємодії між частинками та малої інтенсивності зовнішнього поля. Представлені різні сценарії еволюції популяцій стратегій з пам'яттю, що взаємодіють один з одним у рамках ітерованої дилеми ув'язнених у відкритих та замкнутих системах. Основну увагу приділено колективним характеристикам, таким як пам'ять, рівень агресивності та складність. Обговорюється тонка структура резонансних областей для альфвенових і швидких магнітозвукових хвиль, що використовуються для ВЧ нагрівання в установках КТС. Обговорюється модифікація електродинамічних властивостей середовищ, що стала можливою після появи технологій, що дозволили створювати різні включення в такі середовища. Вивчаються метаматеріали, зокрема шаруваті структури з напівпровідників фериту або тонкі дроти, впроваджені в матрицю. Для вчених у галузі природознавства, викладачів, аспірантів та студентів старших курсів фізичних факультетів.
Проблеми теоретичної фізики. Збірник наукових праць. Випуск 5
Keywords: Research Subject Categories::NATURAL SCIENCES::Physics; features of particle dynamics at cyclotron resonances; effect of fluctuations on the dynamics of particles at cyclotron resonances; new cyclotron resonances; influence of plasma density fluctuations on plasma-beam interaction; self-consistent theory of excitation of waves by beams of oscillators under the conditions of isolated cyclotron resonance; self-consistent theory of excitation of waves by beams of oscillators; isolated cyclotron resonance; particle acceleration by the wave packet field; new resonances in the interaction of charged particles with waves in vacuum; electromagnetic fields; excitation of electromagnetic radiation; interaction of charged particles; dielectric and plasma-like solid media; the reduced description method in the kinetic theory; complex systems of identical particles; strategies with memory; fine structure of the local alfven resonances; cylindrical plasmas; axial periodic inhomogeneity; electromagnetic waves; artificial composite media